Saving Finnegan - Grindley, Sally (Bloomsbury London, 2007)
Set on an island off Scotland, Holly is at the forefront of efforts to save the whale stranded on the beach below her house. The small island community is divided over which course of action to take and Holly finds herself engaged in a battle in which she has some unlikely friends and foes. Suggested level: primary